Examining the Ruggie report: can voluntary guidelines tame global capitalism? - Bittle, Steven (Critical criminology, 2013)
In recent years many academics, social activists and NGOs have turned to international bodies in an attempt to hold corporations accountable for their harmful and illegal acts. Significant amongst these is the UN Special Representative of the Secretary-General on issues of human rights and transnational corporations. In 2008, following extensive research and consultation with states, corporations and civil society groups, the Special Representative released a series of guidelines outlining the responsibilities of states and corporations to respect human rights, and of both to ensure access to effective judicial and non-judicial remedies for victims. This paper argues that the UN guidelines fail to recognize or incorporate the empirically and historically demonstrated imperatives that guide transnational global capitalism. While global capitalism is complex and rife with contradictions, its raison d’etre is rooted in profit maximization. The paper sets out alternative provisions with, we argue, greater potential to subject global capital to the rule of law.